On the use of the equivalent linearization for bilinear oscillators under pulse-like ground motion. (1st April 2018) - Quaranta, Giuseppe; Mollaioli, Fabrizio
Highlights: The peak displacement prediction through equivalent linearization is investigated. The linearization of bilinear oscillators under pulse-like earthquakes is considered. A corrective factor is proposed for near-fault seismic waveforms with mid-large pulse periods. Abstract: The equivalent linearization is a well-known simplified approach for estimating the maximum absolute displacement of inelastic systems, being widely adopted in many technical codes and guidelines. In this regard, the present paper addresses the use of the equivalent linearization to estimate the peak displacement of bilinear oscillators with known displacement ductility subjected to near-fault pulse-like earthquakes. An extensive numerical investigation is initially performed in order to evaluate the accuracy of a recent equivalent viscous damping formulation. The analysis of the obtained numerical results reveals how the predictive capability of the equivalent linear model depends on the ratio between elastic period and pulse period of the ground motion. A corrective factor is then proposed in such a way to improve the prediction of the peak inelastic displacement in case of pulse-like seismic waveforms. Numerical results demonstrate that the proposed correction leads to more robust and accurate estimates, especially for low hardening ratio values and mid-large pulse periods.